2012
DOI: 10.2478/v10078-012-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Game Analysis of Olympic, World and European Championships in Men’s Handball

Abstract: The development of men’s handball was analyzed using data from the Olympic, World and European Championships held within the last eight years. The most obvious change, especially within these last nine tournaments, was that men’s handball was played more dynamically and rapidly, both in attack and defense, especially by European teams. The first aim of this study was to conduct a technical analysis of current handball and to determine factors related to success in this sport discipline. The second aim was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
1
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 4 publications
7
83
1
16
Order By: Relevance
“…The effect of spatial position and time of plays on team performance have been widely studied (Celes, Vojvodic, and Skender, 2012;Foretić et al, 2010;Gutiérrez and Ruiz, 2013;Meletakos et al, 2011). However, other authors suggest that the number of shots per game could be an adequate indicator of team performance (Bilge, 2012). In this line, the present study shows that the number of throws is a significant variable in overall team performance.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The effect of spatial position and time of plays on team performance have been widely studied (Celes, Vojvodic, and Skender, 2012;Foretić et al, 2010;Gutiérrez and Ruiz, 2013;Meletakos et al, 2011). However, other authors suggest that the number of shots per game could be an adequate indicator of team performance (Bilge, 2012). In this line, the present study shows that the number of throws is a significant variable in overall team performance.…”
Section: Discussionsupporting
confidence: 58%
“…Some researchers have highlighted the efficacy of fastbreak, pivot actions, and first line players in team success (Bilge, 2012), while others have shown negative correlations between goal attempts and goals scored in shots from six-and nine-metre (Foretić et al, 2010;Meletakos et al, 2011). Other studies have shown that, in isolation, goalkeeper actions are insufficient to increase the probability of winning a match, and that shot efficacy should be considered.…”
mentioning
confidence: 99%
“…However, an addition effect might have led to greater changes in EIMD markers that would not be manifested after a single match, as previously described in a similar model 22 . However, considering that the most important TH competitions have a short-term, condensed characteristic 23 , it is also important to investigate the level of stress imposed to the neuromuscular system throughout them.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement and assessment of the game actions play an important role in planning the training process and competition (Bilge, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was the edition with most teams participating, 16 in number; at the next edition decreases the number of teams to 11, and from 1980 to the present, the number of participating teams is 12. Designation of participating teams is as follows: the host team, World Cup finalists, winners of continental championships to which there are added the first 2 ranked each of the 3 qualifier tournaments.In the form with 12 participating teams, the number of games played by each team varies between 5 and 8, depending on the place in the rankings: places 1-8 -6-8 games, places 9-12 -5 games.The measurement and assessment of the game actions play an important role in planning the training process and competition (Bilge, 2012).The handball players must have a lot of motor skills enabling them to execute a wide range of techniques, with and without the ball, in terms of speed and strength in relationships with teammates and in opposition with the other team. Practicing handball at performance level requires a specific and sustained effort to meet the rigors of competition (Ghervan, 2006).…”
mentioning
confidence: 99%